In Vitro and Ex Vivo Chemopreventive Action of Mauritia flexuosa Products. (3rd June 2018) - Pereira-Freire, Joilane Alves; Oliveira, George Laylson da Silva; Lima, Layana Karine Farias; Ramos, Carla Lorena Silva; Arcanjo-Medeiros, Stella Regina; Lima, Ana Cristina Silva de; Teixeira, Sabrina Almondes; Oliveira, Guilherme Antônio Lopes de; Nunes, Nárcia Mariana Fonseca; Amorim, Vivianne Rodrigues; Lopes, Luciano da Silva; Rolim, Larissa Araújo; et al.
Abstract : Mauritia flexuosa (Arecaceae), known as "Buriti, " is a Brazilian palm tree with high economic potential for local communities. Herein, we investigated the phytochemistry profile and antioxidant potential of M. flexuosa fruits and determined the bioaccessibility of phenolic compounds. Peels revealed upper values for phenols, flavonoids, carotenoids, tannins, and ascorbic acid when compared to the pulps and endocarps. All samples showed capacity to scavenger free radicals (0.5, 1.0, 2.0, 4.0, and 8.0 mg/mL) but peels presented higher scavenger action in all methods explored. Phenolic compounds identified by HPLC displayed reduced bioaccessibility after in vitro simulated gastrointestinal digestion for pulp (38.7%), peel (18.7%), and endocarp (22.3%) extracts (P < 0.05 ). Buriti fruits also protected rat blood cells against lysis induced by peroxyl radicals. We demonstrated the promising chemopreventive potentialities of M. flexuosa fruits and their by-products and peels with higher quantities of bioactive compounds and phenolic substances before and after in vitro bioaccessibility investigation. In Brazil, these parts are discarded or underused, mainly as feed for ruminant animals. Consequently, it is extremely important to explore nutritional characteristics of these by-products for human/livestock foods and to install biofriendly techniques and sustainable biotechnology handling of natural resources.